Assessment of genetic relationship between Klebsiella pneumoniae and Klebsiella oxytoca samples isolated from a dental office - Pimenta-Rodrigues, M. [UNESP]; Fusco-Almeida, A. M.; Bertoni, B. W.; Pietro, R. C. L. R. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2008)
The present study aimed to analyze the genetic similarity between genomic profiles of thirteen Klebsiella oxytoca and seven Klebsiella pneumoniae samples isolated from two different collections carried out in different places of dental offices. Random amplified polymorphic DNA (RAPD) technique and similarity coefficients (calculated by Sorensen-Dice and simple matching) were applied to determine their genetic profile of randomic DNA sequences. The majority of the isolates of K. pneumoniae and K. oxytoca presented similar coefficient values (>= 0.80). Thus, it was possible to identify that strain dissemination occurred mainly via the hands of the surgeon-dentists and, finally, to determine the genetic similarity of the strains from dental office environments.
Keywords: Klebsiella oxytoca; Klebsiella pneumoniae; RAPD; dental office